The Probative Value of Digital Signatures in Authentic Deeds - R. Dian Luthfiana Harun; Weny Almoravid Dungga; Mohamad Taufiq Zulfikar Sarson (Journal of Law, Human Rights, Immigration, and Corrections, 2026)
This study examines the validity and legal implications of electronic signatures in notarial agreements within the Indonesian jurisdiction. Although the Electronic Information and Transactions Law recognizes electronic signatures as valid legal evidence, their direct application to authentic deeds still faces severe normative constraints under the Notary Public Act. Specifically, the Act firmly mandates the physical presence of all parties, the verbal reading of the deed, and the physical signing before an authorized notary. Utilizing normative legal research and statutory approaches, this analysis demonstrates that employing electronic signatures without careful regulatory harmonization degrades the evidentiary power of authentic deeds, effectively reducing them to mere underhand deeds. This systemic conflict generates profound legal uncertainty while significantly increasing the professional liability risks for notaries nationwide. Therefore, comprehensive statutory synchronization alongside the establishment of definitive implementing regulations remains absolutely essential to support a secure, legally sound, and highly prudent digital transformation of notarization practices.